2020
DOI: 10.21203/rs.3.rs-33569/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of assay method- and trimester-specific reference intervals for thyroid hormones during pregnancy in Chengdu, China

Abstract: Background: The reference intervals of thyroid hormone will change at different stages of pregnancy because of physiological alterations. On the other hand, the reference intervals of hyroid hormone will also change in different detection systems due to manufacturer’s methodology as well as different race. The objective in this study was to establish the assay method- and trimester-specific reference intervals for thyroid stimulating hormone, free thyroxine, and free triiodothyronine for pregnant women in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The clear trend was consistent with previous investigations [32][33][34]. Most previous studies have paid more attention to the cut-off values of TSH in early pregnancy, which is considered to have a considerable impact on fetal development due to immature thyroid glands.…”
Section: Discussionsupporting
confidence: 91%
“…The clear trend was consistent with previous investigations [32][33][34]. Most previous studies have paid more attention to the cut-off values of TSH in early pregnancy, which is considered to have a considerable impact on fetal development due to immature thyroid glands.…”
Section: Discussionsupporting
confidence: 91%
“…They recommended the determination of population-based trimester-specific reference ranges for serum TSH by including pregnant women with no known thyroid disease, optimal iodine intake, and negative antithyroid peroxidase antibody (TPOAb) status, as well as assay method-specific and trimester-specific pregnancy reference ranges for serum FT4. Since 2017 several studies on the reference ranges of thyroid parameters were reported in different countries [7][8][9][10][11][12][13][14][15][16]; however, in Japan limited studies have been reported [17][18][19][20]. In addition, the reference range (5-95th percentile) of TSH we reported in "Erratum" for the original paper [20] was incorrect due to a typographic error [21].…”
mentioning
confidence: 97%